Comparative Study Analysis of the Effect of Protectionism Policy on Indonesian Cocoa Exports to Destination Countries: India, United States, Malaysia, China, Australia - Sofyan, Agus; Apriliana, Tria (Universitas Batanghari Jambi, 2025)
Protectionist policies are taken by some countries such as Indonesia with the aim of protecting and improving the quality of domestic products. Indonesia is one of the largest cocoa producers in the world and plays an important role in the global supply chain. This study aims to analyze the effect of protectionist policies implemented by the Indonesian government on the volume of cocoa exports to five main destination countries, namely India, the United States, Malaysia, China, and Australia, during the 2019-2023 period. Protectionist policies such as export duty tariffs and non-tariff regulations are implemented to encourage domestic processing to increase the added value of cocoa products. The research method uses a quantitative approach with comparative analysis. Data was obtained from reliable secondary sources, such as the Central Statistics Agency (BPS). The results show that protectionist policies have a significant impact on the competitiveness of Indonesian cocoa exports in the global market. The practical implication of this study is the importance of market diversification and product quality improvement to face international competition. In addition, the government needs to balance between protecting the domestic industry and increasing global competitiveness to maintain the sustainability of Indonesian cocoa exports.